2006
DOI: 10.1007/s10646-006-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India

Abstract: The measurement of acetylcholinesterase (AChE) activity is used worldwide as a biomarker of environmental contamination due to neurotoxic substances. In the present study the AChE activities was measured in marine snails (Cronia contracta) collected seasonally from six sampling sites (viz. Arambol, Anjuna, Dona Paula, Vasco, Velsao and Palolem) along the Goa coast during the pre-monsoon (April, 2004), monsoon (September, 2004) and post-monsoon (November, 2004) periods. The AChE activities in C. contracta showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…AChE is widely used as a biomarker in various toxicological studies. 35,36 Seasonal variation in AChE activity in the nervous tissue of the clam Tapes philippinarum. 35 and snail Cronia contracta were noted in different Goa cost of India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AChE is widely used as a biomarker in various toxicological studies. 35,36 Seasonal variation in AChE activity in the nervous tissue of the clam Tapes philippinarum. 35 and snail Cronia contracta were noted in different Goa cost of India.…”
Section: Discussionmentioning
confidence: 99%
“…35 and snail Cronia contracta were noted in different Goa cost of India. 36 It is reported that acetylcholinesterase and cytochrome oxidases are very important enzymes in activation of cercaria. 37 The enzyme AChE plays an important role in animals exposed to various natural/unnatural stimulants and in nerve impulse transmission in both vertebrate and invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Para Gaitonde et al (2006) anticolinesterásicos tais como organofosforados, carbamatos e elementos tóxicos (Cd, Pb, Cu etc) se ligam ao sítio catalítico da enzima AChE, evitando inativação fisiológica da acetilcolina levando a um prolongamento anômalo da neurotransmissão. Assim sendo, o uso da AChE nos tecidos muscular e nervoso de peixes tem sido bastante utilizado para avaliar os efeitos da contaminação, pois essa enzima tem ampla disponibilidade e grande quantidade nestes tecidos (STUMM, 1987;OLIVEIRA, 2007).…”
Section: Acetilcolinesteraseunclassified
“…On the other hand the interest of the use of acetylcholinesterase inhibition as an integrative measurement of the overall neurotoxic risk posed by the whole burden of bioavailable contaminants present in the environment has been received grown attention. Recently, measurements of AChE activity inhibition in fish and aquatic invertebrates as general biomarker of neurotoxicity have been successfully used in a number of field studies [20,[34][35][36].…”
Section: Biomarkers As Tools For Pollutant Expo-sure Detection and Efmentioning
confidence: 99%